Shadows of fear: Extortion and protection racketeering amidst organized crime in South Africa - Mugambiwa, Shingirai; Rakubu, Kholofelo (Edelweiss Applied Science and Technology, 2024)
This paper investigates organized crime networks that engage in extortion and protection racketeering in South Africa. Due to socio-economic hardships and weak institutional frameworks, criminals have employed fear and violence as a means to gain control over local communities and businesses illegally. The study employed a literature analysis of scholarly materials such as peer-reviewed journals, books, and reports by law enforcement agencies and nongovernmental organizations among others to gather knowledge on extortion and protection racketeering in organized crime in South Africa. The study examines the operational strategies and impacts of organised crime networks on extortion and protection racketeering on local economies as well as public safety. The findings review that there is an all-pervasive culture of fear which underlies blackmailing as well as racketeering activities thereby increasing the vulnerability of communities while undermining social cohesion. The paper concludes by recommending policies meant to improve law enforcement capability and community resilience against this threat on communities.